Tailoring the Structural Evolution of Co-Supported Fibrous ZSM-5 via Hydrothermal Aging for Syngas Production in Ethanol Dry Reforming - Nor Shuhada Solehah Hanafi; Asmida Ideris; Aster Rahayu; Martomo Setyawan; Agus Aktawan; Herma Dina Setiabudi; Nurul Ainirazali (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The catalytic dry reforming of ethanol (EDR) offers a promising approach to reduce CO2 emissions and support the less carbon-intensive processes. This study examined the effect of cobalt (Co) loading on fibrous ZSM-5 (FZSM-5), which was synthesized at hydrothermal aging times of 6, 8, and 10 h, for EDR. The catalytic evaluation was carried out at 650 °C, 1 bar, and 30,000 mL.g-1.h-1 for 8 h. The results showed that hydrothermal aging time influenced the catalyst properties and catalytic performance. The catalyst aged for 8 h developed a distinct dendritic structure, a surface area of 208.9 m2.g-1, and distributed hierarchical porosity. During EDR, the 8 h Co/FZSM-5 catalyst sustained stable ethanol conversion and produced a favorable H2/CO ratio of 1.55. By contrast, the 6h catalyst showed low crystallinity, while the 10 h catalyst underwent extended crystal growth that limited mass transfer. TGA results further showed that the 8 h catalyst limited carbon deposition more effectively and exhibited less deactivation better than the other samples. These findings provide practical guidance for catalyst design and support the development of more resource-efficient reforming processes. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).